Drug release behavior of a pH/temperature sensitive calcium alginate/poly(N-acryloylglycine) bead with core-shelled structure (eXPRESS Polymer Letters)
In this study, a novel pH/temperature sensitive hydrogel bead with core-shelled structure, composed of calcium alginate (Ca-alginate) and poly((N-acryloylglycine) (PAG), was prepared using as a drug delivery system. The equilibrium swelling has indicated the distinct sensitivities of the beads to pH value and temperature. In pH = 7.4 phosphate buffer solution (PBS), the cumulative release amount of indomethacin loaded in the core of the beads was about 83.5% within 650 min, whereas this value only reached 16.6% in pH = 2.1 PBS. In addition, the release rate of indomethacin was much faster at 37°C than that at 24°C. The experimental results have showed that the Ca-alginate/PAG beads have a potential application for the pH/temperature-controlled drug release carrier in the biomedical field.